Determination of perceived stress, salivary cortisol and interleukin-1β levels and clinical features of chronic urticaria in patients with dermographic urticaria in comparison to patients with chronic spontaneous urticaria and healthy individuals - Lugović-Mihić, Liborija; Novak-Hlebar, Ina; Smoljan, Dajana; Vukasović, Ines; Barac, Ema; Vilibić, Maja (Frontiers in Immunology, 2026)
IntroductionAlthough dermographic urticaria or symptomatic dermographism (SD), is the most common chronic inducible urticaria subtype, little is known about its etiopathogenesis and associated factors such as psychological stress.MethodsIn this cross-sectional study we included a total of 100 examinees, and compared the data/findings of 34 SD/DU patients to 33 chronic spontaneous urticaria (CSU) patients, and 33 healthy controls. We looked at perceived psychological stress (Perceived Stress Scale/PSS), salivary cortisol and IL-1β levels, clinical characteristics [dermographism activity/severity (on a scale from 1 to 4), disease control (Urticaria Control Test/UCT) and disease activity of CSU patients (Urticaria Activity Score/UAS)], and demographic data.ResultsDermographism activity/severity linearly correlated with perceived stress/PSS (r=0.347; p=0.045), with no correlation with other factors. Disease duration in SD/DU patients was negatively linearly related to salivary cortisol (r=-0.369; p=0.032), but not to IL-1β. In the SD/DU and CSU groups, no significant correlations were observed between salivary cortisol, IL-1β, PSS, and age; however, urticaria severity positively, linearly correlated with perceived stress (p=0.004). Males had higher salivary cortisol (median 1.1 vs. 0.9; p=0.028) and higher IL-1β levels than females (687.6 vs. 408.9 pg/mL; p=0.029), while females had higher perceived stress levels (16 vs. 12; p=0.006). CSU patients had significantly higher disease control than the SD/DU group (moderate effect size) (p=0.001). In SD/DU patients with concomitant allergies, lower cortisol values were recorded (moderate effect size) (median log 1.03 vs. 0.80 nmol/L; p=0.032) and disease lasted longer than in those with no allergies (a large effect size) (48 vs. 18 months; p=0.002). In SD/DU patients with associated conditions/diseases, their SD/DU lasted significantly longer than for those without comorbidities (60 vs. 24 months; p=0.017).ConclusionSince stress is often perceived by SD/DU patients and affects SD/DU activity/severity, psychological support could be beneficial for these patients.